Crystallographic structure of LiFe1−xMnxPO4 solid solutions studied by neutron powder diffraction. Issue 3 (11th March 2014) - Li, X.Y.; Zhang, B.; Zhang, Z.G.; He, L.H.; Li, H.; Huang, X.J.; Wang, F.W.
Abstract : High-resolution neutron powder diffraction (NPD) data were recorded on a series of cathode material LiFe1− x Mn x PO4 ( x  = 0, 0.2, 0.5, 0.8, and 1.0) solid solutions using the HRPD machine at SINQ/PSI, Switzerland. Ab initio crystal structure solution via program FOX indicates demonstrably that the space group of LiFePO4 is Pnma with Li 1+ occupying octahedral (4a) sites and Fe 2+ octahedral (4c) sites, respectively, in the olivine structure. Rietveld refinement (program FullProf suite version July-2011), complementary with X-ray diffraction data, shows that Fe 2+ may partially (about 2%) distribute over Li 1+ sites. NPD data for LiFe1− x Mn x PO4 ( x  = 0, 0.2, 0.5, 0.8, and 1.0) reveal that the Mn 2+ replaces Fe 2+ at the octahedral (4c) sites. The cell parameters a, b, and c increase linearly and the interatomic distances (in Å) of Li–O(2) and Li–O(1) increase, while the interatomic distances (in Å) of Li–O(3) decrease on the addition of Mn, respectively, partially explaining a higher potential plateau of ~4.1 eV in LiMnPO4 compared to ~3.5 eV in LiFePO4 .